ANALISIS STILISTIKA KATA AL-DĪN, AL-DĪN AL-QAYYIM, AL-DĪN AL-KHĀLIṢ, DĪNILLĀH DAN MILLAH DALAM AL-QUR’AN - Hakim, Faridl; Hardiyanti, Putri; Delami (AL ITQAN: Jurnal Studi Al-Qur'an, 2022)
This article discusses the style in the mention of religion (Al-Dīn, Al-Dīn Al-Qayyim, Al-Dīn Al-Khāliṣ, Dīnillāh and Millah) in the Qur'an. The theory used in this article is a study of stylistic. Stylistics is the study of language in the content of speech structures, also examines the speech that is distributed among various types/nations/ethnic personalities. The result of this research is the identification of aspects (grammar, historical and interpretation) that can be revealed meanings (Al-Dīn, Al-Dīn Al-Qayyim, Al-Dīn Al-Khāliṣ, Dīnillāh and Millah). The results in this study, firstly, the position of the sentence Al-Dīn has a position as maf’ūl bihi (object), Al-Dīn Al-Qayyim as ṣifah-mauṣūf (descriptive-adjective), Al-Dīn Al-Khāliṣ as a descriptive-adjective, Dīnillāh as Iḍāfah (annexation) and Millah as maf’ūl bihi whose verb is discarded. The scondly, content of speech in the sentence (Al-Dīn, Al-Dīn Al-Qayyim, Al-Dīn Al-Khāliṣ, Dīnillāh and Millah) which have the same meaning or variety, namely religion that is kāffah (complete), perfect, savior and bringer of happiness.